A comparative study of the determinants of capital structure in shipping companies: the case of Korea and Greece. Issue 4 (19th May 2022) - Yang, Huckjun; Lee, Kihwan; Lim, Sangseop
ABSTRACT: Shipping companies need a huge amount of external funds to purchase ships, and financing choices have a decisive effect on a firm's valuation. Capital structure decisions are of great importance for maximizing corporate value which is the primary goal of financial management. Therefore, this study investigates the differences of capital structure decisions in Korean and Greek shipping companies using a sample of 60 Korean and 32 Greek shipping companies in terms of shipping business models: an operator model and an owner model. The result shows that Korean and Greek shipping companies follow the pecking order theory, and the two countries indicate different results of capital structure regressions including supply and demand factors with their unique shipping business models.